PERAN BUDAYA MASYARAKAT ISLAM JAWA TERHADAP KERUKUNAN UMAT BERAGAMA - Huda, Dimyati (P3M IAIN KEDIRI, 2017)
Look at the fact that the conflict is still going on then the need for handling conflicts, especially religious conflicts with the way enhance the religious harmony that live in the Earth Indonesia with diverse cultures and beliefs. With a strategy how to let religious unity could increase and coexist as expected of mankind. This research will be done in Blitar Regency, why so? In addition to the restriction of the problem, since in the County there are majority religion of Islam which is closely linked to the traditions of Java in keseharianya and terdapat variants of religion and places of worship that looks very harmonious. As for the purpose of this research is to mendiskripsikan the findings the role of popular culture in Islamic religious unity against Java. The results of this research is to boost religious harmony Lo need an understanding of the functional theory of the latter is that humans have a sense of berdayaan because of the very limited human presence, ability, time, power will limited by the ability of mankind in control and affect the condition of the desire of her life. In order to realize the religious harmony it is necessary policy leadership in favour of the people Key word: Culture, Harmony, Islam of Java